Dampak Asap Rokok dan Asap Vape pada Pernapasan - Shalahuddin, Muhammad Abdurrahman; Malik, Sansan Abdul (Neolectura, 2023)
Cigarette smoke and vaping have grown to become significant public health concerns around the world. Both types of cigarettes have various chemicals that can impact the respiratory system and overall health. E-cigarettes or vapes are often considered a safer alternative, but in fact, they can also be harmful to respiratory health. This research aims to explore and compare the impact of cigarette smoke and vape smoke on the respiratory system. The research used a qualitative approach with a literature review method. This approach was chosen because it allowed the researcher to collect and analyze information from a variety of existing sources, thus providing a comprehensive view of the topic at hand. The results of this study explain that both cigarette smoke and vape smoke have significant impacts on respiratory health, with cigarette smoke linked to chronic obstructive pulmonary disease (COPD) and lung cancer, while vape smoke although considered safer, still carries serious health risks including inflammation and lung tissue damage.